Permainan Pesan Berantai dalam Pembelajaran Nahwu di Pondok Pesantren Darul Huda Litahfidzil Qur'an Gondanglegi - Eka Silfia Khumairah; Muassomah (Al-Jawhar : Journal of Arabic Language, 2023)
Nahwu learning is part of learning Arabic. It is often found that students feel sleepy or bored while learning nahwu is carried out compared to other learning such as istima' or kalam, but learning nahwu will be more fun if learning is applied with games. So this research discusses the chain message game in nahwu learning, and this chain message game hones students' ability to remember learning material and makes students feel fun in the learning process. The purpose of this study is to find out the implementation of the chain message game in nahwu learning, which is applied at the Darul Huda Islamic Boarding School, and to know the advantages and disadvantages of this game. The method used in this research is descriptive qualitative method. Data collection was carried out, namely interviews and observations, then data analysis techniques were carried out using the Miles & Huberman interactive analysis model. Data collection from this study was carried out from the learning process at the Darul Huda Islamic Boarding School. The results of this study are (1) the implementation of a chain message game in nahwu learning at the Darul Huda Litahfidzil Qur'an Gondanglegi Islamic Boarding School, namely there are six stages. In the first stage, the teacher prepares learning materials. Second, the teacher prepares paper media. Third, the division of groups. Fourth, groups consist of 3 or 4 people and line up. Fifth, each group gets 1 paper containing instructions. Sixth, students run the game. (2) the advantages and disadvantages of this game are that the advantages are easy to understand, students are more confident, remember the material, and are efficient. While the drawback is that you have to have enough time so that the implementation does not tend to be rushed.